Antimicrobial Potential of Pithecellobium dulce Seed Extract against Pathogenic Bacteria: In Silico and In Vitro Evaluation. (4th February 2023) - Aldarhami, Abdu; Bazaid, Abdulrahman S.; Alhamed, Abdullah S.; Alghaith, Adel F.; Ahamad, Syed Rizwan; Alassmrry, Yasseen A.; Alharazi, Talal; Snoussi, Mejdi; Qanash, Husam; Alamri, Abdulwahab; Badraoui, Riadh; Kadri, Adel; et al.
Abstract : Clinical multi-drug-resistant bacteria continue to be a serious health problem. Plant-derived molecules are an important source of bioactive compounds to counteract these pathogenic bacteria. In this paper, we studied the chemical composition of the methanol (80%) extract from Pithecellobium dulce seed (Hail, Saudi Arabia) and its ability to inhibit the growth of clinically relevant multi-drug-resistant bacteria. Molecular docking analysis was performed to predict the best compounds with low binding energy and high affinity to interact with two Staphylococcus aureus receptors. Data showed that P. dulce extract is a rich source of D-turanose (55.82%), hexadecanoic acid (11.56%), indole-1-acetic acid (11.42%), inositol (5.78%), and octadecanoic acid (4.36%). The obtained extract showed antibacterial activity towards tested clinical bacterial strains with MIC values ranging from 233 mg/mL for Acinetobacter baumannii to 300 mg/mL for S. aureus and Escherichia coli . Turanose interaction has resulted in -7.4 and -6.6 kcal/mol for 1JIJ and 2XCT macromolecules, while inositol showed energy values (−7.2 and −5.4 kcal/mol) for the same receptors. Multiple identified compounds showed desirable bioavailability properties indicating its great potential therapeutic use in human. Overall, current investigation highlights the possible use of P. dulce extract as a valuable source for drug development against pathogenic drug-resistant bacteria.